A 2D channel potential modelling of symmetric double-gate MOSFET at onset of threshold condition. Issue 1 (2nd January 2021) - Bose, Ria; Roy, J. N.
ABSTRACT: A two-dimensional (2D) channel potential distribution is analytically derived for lightly doped double-gate MOSFET at turn-on condition of the device by solving 2D Poisson's equation with the application of suitable boundary condition. Threshold voltage roll-off is also modelled to predict the short channel behaviour of the device at sub-threshold condition. Our derived model closely follows the 2D numerical simulation without the inclusion of any fitting parameters. It also serves as a basic step towards computing the compact modelling of DG MOSFET at threshold condition.